2015
DOI: 10.1097/spv.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Compromise in Laparoscopic Versus Vaginal Uterosacral Ligament Suspension

Abstract: We found a lower rate of ureteral compromise in the laparoscopic approach to USLS compared with the traditional vaginal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…This shortened length of admission was notable because 87% of patients underwent hysterectomy; however, 38% were discharged on postoperative day 0 and 60% were discharged on postoperative day 1. In addition, there was no ureteral injury or compromise in the L-USLS cohort, which is consistent with prior studies that report a 0% rate of ureteral compromise [6,[10][11][12]. The low rate of ureteral injury is postulated to be due to the laparoscopic approach allowing visualization of the ureter course to avoid ureter injury or kinking.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This shortened length of admission was notable because 87% of patients underwent hysterectomy; however, 38% were discharged on postoperative day 0 and 60% were discharged on postoperative day 1. In addition, there was no ureteral injury or compromise in the L-USLS cohort, which is consistent with prior studies that report a 0% rate of ureteral compromise [6,[10][11][12]. The low rate of ureteral injury is postulated to be due to the laparoscopic approach allowing visualization of the ureter course to avoid ureter injury or kinking.…”
Section: Discussionsupporting
confidence: 88%
“…The laparoscopic approach to USLS (L-USLS) is gaining more widespread use because it allows full visualization of the uterosacral ligament, allowing suspension at a higher point along the uterosacral ligament. Studies comparing L-USLS to V-USLS showed a lower risk of ureteral compromise compared to V-USLS [4][5][6]. In addition, Turner et al found no significant difference in prolapse recurrence between L-USLS and V-USLS [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was no ureteral injury or compromise in the L-USLS cohort, which is consistent with prior studies that report a 0% rate of ureteral compromise. 6,[10][11][12] The low rate of ureteral injury is postulated to be due to the laparoscopic approach allowing visualization of the ureter course to avoid ureter injury or kinking. This is a potential advantage over V-USLS as it has been associated with a 3-8% incidence of ureteral compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing L-USLS to V-USLS showed a lower risk of ureteral compromise compared to V-USLS. [4][5][6] In addition, Turner et al found no signi cant difference in prolapse recurrence between L-USLS and V-USLS. 7 To date, there are no studies comparing perioperative complications and surgical outcomes between L-USLS and SSLF to guide patient counseling.…”
Section: Introductionmentioning
confidence: 98%
“…Ureteral obstruction in vaginal USL varies from 1-11%, which can be minimized by suturing deep in the intermediate third of the uterosacral ligament or performing the procedure abdominally where the ureter can be more easily freed and visualized [15][16][17][18]. There has been shown to be minimal ureter obstruction with laparoscopic USL [19]. Nerve injuries can occur as the visceral fibers of the inferior hypogastric plexus in the S2-3 dermatome have been shown to be associated with USL and rarely require suture removal [20].…”
Section: Prolapsementioning
confidence: 99%